2018
DOI: 10.3382/ps/pex265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of production system (barn and free range) and slaughter age on some production traits of guinea fowl

Abstract: A total of 200 guinea fowl was reared in either barn or free-range systems and slaughtered at 14, 16, or 18 wk of age in order to determine the effects of production system on live weight, feed consumption, and some carcass and slaughter traits. Production system had a significant effect on live weight until 14 wk of age. Live weights were similar between free-range and indoor production systems at 16 (1,150 g vs. 1,152 g) and 18 (1,196 g vs. 1,203 g) wk of age. Guinea fowl reared in a free-range system consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
14
0
4
Order By: Relevance
“…The evaluation of meat quality included pH measurement (15, 60 min, and 24 h after slaughter) with the use of pH meter CP-251, water-holding capacity according to Grau and Hamm (1953) method, natural drip loss (Lundstrom and Malmfors, 1985), and thermal (cooking) loss (Yang et al, 2006). Cuboid cores (1 cm×1 cm×2 cm of edge length) were cut from the heat-treated muscles, parallel to the longitudinal orientation of the muscle fibers.…”
Section: Meat Qualitymentioning
confidence: 99%
“…The evaluation of meat quality included pH measurement (15, 60 min, and 24 h after slaughter) with the use of pH meter CP-251, water-holding capacity according to Grau and Hamm (1953) method, natural drip loss (Lundstrom and Malmfors, 1985), and thermal (cooking) loss (Yang et al, 2006). Cuboid cores (1 cm×1 cm×2 cm of edge length) were cut from the heat-treated muscles, parallel to the longitudinal orientation of the muscle fibers.…”
Section: Meat Qualitymentioning
confidence: 99%
“…Meat quality of captured/ hunted (Hofbauer et al 2010) or intensively reared (Kokoszynski et al 2012) pheasants was investigated in previous studies. On the other hand, it was reported that by raising game birds under free-range systems, they could have a taste more similar to game-bird meat (Yamak et al 2018). Meat quality of pheasants reared in extensive system was given by Franco & Lorenzo (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Carcasses were chilled for 24 h at 4°C and cut into parts according to standard methods. Carcass weight (CW), ratio (CR, %), Breast weight (BW, g) and ratio (BR, %), abdominal fat weight (AFW, g) and ratio (AFR, %) were determined from cold carcass (Yamak et al, 2017). Equation of breast index (BI), (BWD*BL) was used (Xu et al, 2018).…”
Section: Data Collectionmentioning
confidence: 99%